2017
DOI: 10.1111/jade.12138
|View full text |Cite
|
Sign up to set email alerts
|

‘I – from dreams to reality’: A Case Study of Developing Youngsters’ Self‐Efficacy and Social Skills through an Arts Educational Project in Schools

Abstract: This is a case study of a one‐year arts educational project ‘I – from dreams to reality’ in which artists worked at school with teachers and learning at the school was planned through arts‐based, co‐operative teamwork during one extra school year of 10th grade students in Finnish basic education. The theme of the year was ‘I’, and so the project was designed to highlight everyone's own way of thinking and expressing art. The research task was to determine whether long‐term holistic arts pedagogy and artist co‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These findings have profound educational implications and contribute to a better understanding of group improvisation and musical creativity as a dialogic practice (Bautista et al, 2018). Such implications resonate with Ruokonen (2018), who showed that artistic projects involving artists, teachers, and students working together have the potential to enhance development of creative thinking and well-being.…”
Section: Pedagogical Keys To Foster Musical Creativitymentioning
confidence: 56%
See 3 more Smart Citations
“…These findings have profound educational implications and contribute to a better understanding of group improvisation and musical creativity as a dialogic practice (Bautista et al, 2018). Such implications resonate with Ruokonen (2018), who showed that artistic projects involving artists, teachers, and students working together have the potential to enhance development of creative thinking and well-being.…”
Section: Pedagogical Keys To Foster Musical Creativitymentioning
confidence: 56%
“…The participants worked in a large classroom where they could flexibly rearrange the display of the materials and resources available, brainstorm and try out ideas, hold debates, and make group decisions (Vecchi, 2010). In sum, drawing on a solid body of prior music creativity research (Beghetto & Kaufman, 2014;Muhonen, 2014;Nouri & Farsi, 2018;Reybrouck et al, 2009;Ruokonen, 2018;Vecchi, 2010;Veloso, 2017), we argue that the combination of the above-mentioned characteristics had the potential to facilitate collective musical creativity.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…b Effect size d z was not available and it could not be calculated from the results reported in the study. c Ruokonen (2018) did not compute a sum score. Instead, the analysis was conducted for each self-efficacy item separately.…”
Section: Resultsmentioning
confidence: 99%